Emission of greenhouse gases in the land use change for sugarcane production in the Center-South region of Brazil - Dias, Naissa Maria Silvestre (2018)
The Earth\'s atmosphere is warming due to a combination of natural effects and anthropic activities, which are directly related to the increment of greenhouse gas (GHG) emissions by burning fossil fuel. Brazil stands out in the world economic scenario as the main producer of ethanol, from sugar cane, considered a source of clean, renewable and economically viable energy. The expansion of this crop into pasture areas, in the Center-South region of Brazil, and the intensification in the production of this biofuel to supply the market have raised concerns about its sustainability. The agricultural is one of the main sectors responsible for the emission of GHG into the atmosphere, therefore, more studies are needed about how land use change (LUC) and production intensification, mainly due to the application of agricultural inputs rich in carbon and nitrogen, can affect GHG emissions. In the Center-South region of Brazil, the main LUC is composed of the succession native vegetation areas to pasture, and in sequence to sugarcane. Therefore, two studies were carried out aiming to determine soil GHG emissions under different land uses in the Center-South region of Brazil (Valparaíso-SP), as well as to characterize the emission factor of the main agricultural inputs in either sugarcane planting or ratoon areas. In the first study, three different land use areas were evaluated, composed of native vegetation, pasture and sugarcane. Among the land uses evaluated in this study, the soil under pasture exhibited the highest emission of carbon equivalents (CO2-eq), which was 41-fold higher than under native vegetation and 5.6-fold higher than under sugarcane. In the second study, two experiments were set up to determine the soil GHG emission fluxes after the application of sources of carbon and nitrogen during sugarcane cultivation. Experiment I: set up in a sugarcane planting area with application of ammonium nitrate, limestone and filter cake, in addition to a control treatment without application of any input. Experiment II: set up in a sugarcane ratoon area with application of vinasse and urea in the first year, and vinasse in the second year. In the first experiment, the soil tillage during the planting process produced a larger increase of soil GHG emissions when compared to the sugarcane ratoon area. Among the inputs applied to the cane plant, filter cake or ammonium nitrate produced the highest GHG emissions from the soil. On the other hand, in the area of sugarcane ratoon, the highest emissions were observed with the application of a combination of organic and mineral fertilizers (vinasse and urea), but with the application of only vinasse, the emission increment was less intense. The emission factors for C-CO2 and N-N2O reported by the IPCC are higher than those observed in this study, in the Center-South region of Brazil. The highest emission factor was observed for ammonium nitrate, with 0.13% for N-N2O in the rainy season. Thus, the expansion of sugarcane planted areas plays an important role in GHG emission. New studies on this contribution to GHG emissions are urgently needed in different regions around the world, in order to define measures to limit emissions and aiming at maintaining the sustainability of this biofuel